SOME GEOMETRIC PROPERTIES OF A NEW SEQUENCE SPACE - Karakas, Murat; Cinar, Muhammed; Et, Mikail (Eudoxus Press, Llc, 2013)
In this paper, we introduce a new sequence space denoted by m (phi,p, u, Delta(r)(v)) and give some properties of this sequence space. Also, we examine Banach-Saks property of type p for this space. Finally, we find Gurarii's modulus of convexity and so show that the sequence space m (phi, p, u, Delta(r)(v)) is uniformly and strictly convex.
Keywords: Difference sequence; Banach-Saks property; uniform convexity; strict convexity; Gurarii's modulus of convexity